2021
DOI: 10.3389/fmed.2021.716086
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Initiation of ECMO Is Associated With Poor Outcomes in Patients With Severe COVID-19: A Multicenter Retrospective Cohort Study

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) is a rapidly evolving therapy for acute lung and/or heart failure. However, the information on the application of ECMO in severe coronavirus disease 2019 (COVID-19) is limited, such as the initiation time. Especially in the period and regions of ECMO instrument shortage, not all the listed patients could be treated with ECMO in time. This study aimed to investigate and clarify the timing of ECMO initiation related to the outcomes of severe patients with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…If initiated at a later stage, it is possible that V-V ECMO is unlikely to improve the substantial fibrotic lung damage that has already manifested due to severe ARDS. Although our data do not provide definitive evidence of this, other studies have reported increased survival rates when early V-V ECMO is initiated (7,8).…”
Section: Discussioncontrasting
confidence: 84%
“…If initiated at a later stage, it is possible that V-V ECMO is unlikely to improve the substantial fibrotic lung damage that has already manifested due to severe ARDS. Although our data do not provide definitive evidence of this, other studies have reported increased survival rates when early V-V ECMO is initiated (7,8).…”
Section: Discussioncontrasting
confidence: 84%
“…As in France in the early stages of the pandemic ( 23 ), even if not explicitly documented, these triage procedures probably took place, especially during July–August 2021, when the number of infected persons and deaths soared. From a clinical perspective, delays in treatment initiation have been reported to lead to poor outcomes ( 24 ). It is also possible that frail older case-patients were more affected by delays in treatment initiation because of healthcare burden.…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of the VV-ECMO (3 interquartile range (IQR) 2-5 days) when compared to late (0.5 interquartile range (IQR) 0-1 days) had shown improved mortality, which was 8.375 days in our series (7). Mortality in covid-ECMO patients ranged from 30 to 95% when initiated late due to resource limitations (trained personnel, delayed transport/ referral to designated centers, and ethical considerations) in addition to patients decompensating before initiation due to progressive lung brosis (8).…”
Section: Discussionmentioning
confidence: 53%